Odmieniona: Wizerunek Marii Komornickiej z perspektywy (auto)biografikcji - Krawczyk, Wiktoria (2025)
CHANGED: THE IMAGE OF MARIA KOMORNICKA FROM THE PERSPECTIVE OF (AUTO)BIOGRAFICTIONStudies on the diversity of Maria Komornicka’s cultural attire grew out of the concept of (auto)biografiction in the approach of Stephen Reynolds and Max Saunders. The subject of interest was the „Changeling” attire permanently adopted by the poet on a July night in 1907, the ambiguity of which inspire several different interpretations. Komornicka’s adoption of attire that was socially and culturally assigned to men at that time (she burns women’s dresses, dons men’s clothing and proclaims herself the incarnation of Piotr Włast’s descendant, giving herself a male name and the nickname „Changeling”) is in fact an escape into human creation in general. This is where all the „deformations” of form in her attire originate from: from androgyne to an angel (as the most perfect embodiment of androgyne), and then to a child (as an asexual being). In each of the works submitted to comparative analysis – the theatre play White Marriage by Tadeusz Różewicz (1973), the film White Marriage by Magdalena Łazarkiewicz (1992), the stage work Book of Em by Izabela Filipiak (2005), and the fictionalized biography Different from Myself by Brygida Helbig (2016) – the use of (auto)biografiction research reveals, on the one hand, the diversity of the representations of Komornicka that appear in them. On the other hand, the multiplicity of paths leading to their modulated versions by expanding the space adjacent to it through what determines their generic opacity, in a sense translating into the genological intricacy embedded in the matter of the texts. The first chapter revolves around the definition of the concept of (auto)biografiction, its genesis, components taken from Komornicka/Włast’s work and beyond. Their presence in the source materials determines that they can be described as experiments with the (life)writing of Maria Komornicka / Piotr Odmieniec Włast from the 19th century to the present. The second chapter outlines the figure of Komornicka/Włast in the light of her/his legacy and the memory of her/ his contemporaries. The third chapter is a synthetic review of the previous findings on the works of the author of The Devils from a critical perspective. The fourth chapter, which is more extensive in its content than the previous ones, focuses on exposing the similarities and discrepancies in the way the poet perceives the ultimately undefined creation of the „Changeling”.
Keywords: (auto)biografiction; gender identity; cultural image; Maria Komornicka; Piotr Odmieniec Włast; Izabela Filipiak; Brygida Helbig; Magdalena Łazarkiewicz; Tadeusz Różewicz